High-resolution variability of dissolved and suspended organic matter in the Cape Verde Frontal Zone - Campanero, Rubén; Burgoa, Nadia; Fernández-Castro, Bieito; Valiente, Sara; Nieto-Cid, Mar; Martínez-Pérez, Alba M.; Gelado-Caballero, María Dolores; Hernández-Hernández, Nauzet; Marrero-Díaz, Ángeles; Machín, Francisco; Rodríguez-Santana, Ángel; Hernández-García, Inés; et al. (Frontiers in Marine Science, 2022)
Distributions of dissolved (DOM) and suspended (POM) organic matter, and their chromophoric (CDOM) and fluorescent (FDOM) fractions, are investigated at high resolution (< 10 km) in the Cape Verde Frontal Zone (CVFZ) during fall 2017. In the epipelagic layer (< 200 m), meso- and submesoscale structures (meanders, eddies) captured by the high resolution sampling dictate the tight coupling between physical and biogeochemical parameters at the front. Remarkably, fluorescent humic-like substances show relatively high fluorescence intensities between 50 and 150 m, apparently not related to local mineralization processes. We hypothesize that it is due to the input of Sahara dust, which transports highly re-worked DOM with distinctive optical properties. In the mesopelagic layer (200-1500 m), our results suggest that DOM and POM mineralization occurs mainly during the transit of the water masses from the formation sites to the CVFZ. Therefore, most of the local mineralization seems to be due to fast-sinking POM produced in situ or imported from the Mauritanian upwelling. These local mineralization processes lead to the production of refractory CDOM, an empirical evidence of the microbial carbon pump mechanism. DOM released from these fast-sinking POM is the likely reason behind the observed columns of relatively high DOC surrounded by areas of lower concentration. DOM and POM dynamics in the CVFZ has turned out to be very complex, in parallel to the complexity of meso- and submesoscale structures present in the area. On top of this high resolution variability, the input of Sahara dust or the release of DOM from sinking particles have been hypothesized to explain the observed distributions.